Pre-existing atrial fibrillation and risk of arterial thromboembolism and death following pneumonia: a population-based cohort study - Reimar Wernich Thomsen; Christian Fynbo Christiansen; Bodil Steen Rasmussen; Lars Hvilsted Rasmussen; Jacob Gamst (BMJ Open)
Objectives To examine the effect of pre-existing atrial fibrillation (AF) and associated therapy on the risk of arterial thromboembolism (ATE) and death following pneumonia.Design, setting and participants Population-based cohort study (1997–2012) of 88 315 patients with first-time hospitalisation with pneumonia in Northern Denmark.Results Of the included patients (median age 73.4 years), 8880 (10.1%) had pre-existing AF. The risk of ATE within 30 days of admission was 5.2% in patients with AF and 3.6% in patients without AF. After adjustment for higher age and comorbidity, the adjusted HR (aHR) with AF was 1.06 (95% CI 0.96 to 1.18). Among patients with AF, reduced risk of ATE was observed in vitamin-K antagonist users compared with non-users (aHR 0.74 (95% CI 0.61 to 0.91)). Thirty-day mortality was 20.1% in patients with AF and 13.9% in patients without AF. Corresponding 1-year mortalities were 43.7% and 30.3%. The aHRs for 30-day and 1-year mortality with AF were 1.00 (95% CI 0.94 to 1.05) and 1.01 (95% CI 0.98 to 1.05). In patients with AF, reduced mortality risk was observed in users of vitamin-K antagonists (aHR 0.70 (95% CI 0.63 to 0.77)) and β-blockers (aHR 0.77 (95% CI 0.70 to 0.85). Increased mortality was found in digoxin users (aHR 1.16 (95% CI 1.06 to 1.28)).Conclusions Pre-existing AF is frequent in patients hospitalised with pneumonia and a marker of increased risk of ATE and death, explained by higher patient age and comorbidity. Prognosis is closely related to preadmission medical treatment for AF.